2007
DOI: 10.1002/pssb.200675148
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of Fe doped SiC crystals

Abstract: In this paper we report on the crystal growth and magnetic as well as structural studies of SiC : Fe. SiC crystals were grown by Physical Vapor Transport method. We used Fe enriched source material to dope crystals. The magnetic properties were examined by AC/DC magnetometry. AC magnetic susceptibility as well as DC magnetization measurements revealed ferromagnetic type of magnetic ordering. The structural measurements using powder X-ray diffraction were performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…A series of SiC:TM ͑TM = Mn, Fe, Co, Cr, etc.͒ have been synthesized and investigated by several research groups. [7][8][9][10][11][12][13][14] For DMSs, such as SiC:TM, there still exist two challenges: ͑1͒ the realization of Curie temperature ͑T c ͒ around or above RT; ͑2͒ whether the obtained material is indeed a solid solution of Si 1−x TM x C or it remains as SiC matrix with embedded TM clusters, precipitates, or second phases that are responsible for the observed magnetic properties. Toward this role, more efforts are required.…”
mentioning
confidence: 99%
“…A series of SiC:TM ͑TM = Mn, Fe, Co, Cr, etc.͒ have been synthesized and investigated by several research groups. [7][8][9][10][11][12][13][14] For DMSs, such as SiC:TM, there still exist two challenges: ͑1͒ the realization of Curie temperature ͑T c ͒ around or above RT; ͑2͒ whether the obtained material is indeed a solid solution of Si 1−x TM x C or it remains as SiC matrix with embedded TM clusters, precipitates, or second phases that are responsible for the observed magnetic properties. Toward this role, more efforts are required.…”
mentioning
confidence: 99%
“…The coercivity of the as-deposited sample is found to be~2.9 × 10 3 A/m which significantly increases to~11.5 × 10 3 A/m for annealed sample at 1073 K, with increase in annealing temperature from 1073 to 1273 K, it decreases to~5.6 × 10 3 A/m. The low coercivity of as-deposited Fe-SiC thin films ascribed to the amorphous nature [24], while the high coercivity of annealed Fe-SiC thin films (1073 K) may be due to the crystalline nature and formation of Fe 3 Si phase [5,19,[25][26][27]. The decrease in coercivity with increase in annealing temperature may be associated with change in grain size.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, singlephase Si 1−x Fe x C bulk material has not been obtained until this study. Here, aluminium element is speculated to play the key role of stabilizing the codoped SiC crystal structure as 4H-single phase and codoping Al and Fe elements could reduce the system energy more effectively than the formation of Fe 3 Si [27,28,32]. Thus, single-phase (Al, Fe)-codoped 4H-SiC offers a chance to investigate the intrinsic magnetic features of Fe-doped SiC and also suggests that (1) the ability to resist the polytypes in SiC is enhanced significantly via doping Al since doping 1.7 at% Fe still does not break the single-phase structure;…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Song et al observed the coexistence of 6H-SiC and 15R-SiC phases in Mn-doped 6H-SiC [26]; (4) TM elements often react with Si or C atoms to form the magnetic secondary phases: binary (ternary) carbides or silicides. Kuryliszyn-Kudelska et al [27] reported the formation of Fe 3 Si in Fe-doped SiC crystals while Song et al [28] found similar results in Fe-doped 6H-SiC powder samples. The presence of Fe 3 Si, a FM material with a T c of 837 K, makes it impossible to probe the natural magnetic properties of Fe-doped SiC embeded in the mixture.…”
Section: Introductionmentioning
confidence: 88%